Innate Immunity to Legionella Pneumophila - Massis, Liliana M.; Zamboni, Dario S. (Frontiers in Microbiology, 2011)
Innate immune cells, such as macrophages, are highly adapted to rapidly recognize infections by distinct pathogens, including viruses, bacteria, fungi and protozoa. This recognition is mediated by pattern recognition receptors (PRRs), which are found in host cell surface membranes and the host cell cytoplasm. PRRs include protein families such as the Toll-like receptors (TLRs), Nod-like receptors (NLRs), RIG-I-like receptors (RLRs) and sensors of cytosolic DNA. The activation of these PRRs by pathogen-associated molecular patterns (PAMPs) leads to transcriptional responses and specific forms of cell death. These processes effectively contribute to host resistance to infection either via cell-autonomous processes that lead to the intracellular restriction of microbial replication and/or by activating pathogen-specific adaptive immune responses. L. pneumophila, the causative agent of Legionnaires’ Disease, is a Gram-negative bacterium that triggers responses by multiple PRRs. Here, we review a set of studies that have contributed to our specific understanding of the molecular mechanisms by which innate immune cells recognize and respond to L. pneumophila and the importance of these processes to the outcome of infection.